Unrelated donor versus matched sibling donor in adults with acute myeloid leukemia in first relapse: an ALWP-EBMT study - Ruggeri, Annalisa; Battipaglia, Giorgia; Labopin, Myriam; Ehninger, Gerhard; Beelen, Dietrich; Tischer, Johanna; Ganser, Arnold; Schwerdtfeger, Rainer; Glass, Bertram; Finke, Jurgen; Michallet, Mauricette; Stelljes, Matthias; et al. (Journal of hematology & oncology, 2016)
BACKGROUND: Allogeneic stem cell transplantation is the only curative option for patients with acute myeloid leukemia (AML) experiencing relapse. Either matched sibling donor (MSD) or unrelated donor (UD) is indicated. METHODS: We analyzed 1554 adults with AML transplanted from MSD (n = 961) or UD (n = 593, HLA-matched 10/10, n = 481; 9/10, n = 112). Compared to MSD, UD recipients were older (49 vs 52 years, p = 0.001), transplanted more recently (2009 vs 2006, p = 0.001), and with a longer interval to transplant (10 vs 9 months, p = 0.001). Conditioning regimen was more frequently myeloablative for patients transplanted with a MSD (61 vs 46 %, p = 0.001). Median follow-up was 28 (range 3-157) months. RESULTS: Cumulative incidence (CI) of neutrophil engraftment (p = 0.07), grades II-IV acute GVHD (p = 0.11), chronic GVHD (p = 0.9), and non-relapse mortality (NRM, p = 0.24) was not different according to the type of donor. At 2 years, CI of relapse (relapse incidence (RI)) was 57 vs 49 % (p = 0.001). Leukemia-free survival (LFS) at 2 years was 21 vs 26 % (p = 0.001), and overall survival (OS) was 26 vs 33 % (p = 0.004) for MSD vs UD, respectively. Chronic GVHD as time-dependent variable was associated with lower RI (HR 0.78, p = 0.05), higher NRM (HR 1.71, p = 0.001), and higher OS (HR 0.69, p = 0.001). According to HLA match, RI was 57 vs 50 vs 45 %, (p = 0.001) NRM was 23 vs 23 vs 29 % (p = 0.26), and LFS at 2 years was 21 vs 27 vs 25 % (p = 0.003) for MSD, 10/10, and 9/10 UD, respectively. In multivariate analysis adjusted for differences between the two groups, UD was associated with lower RI (HR 0.76, p = 0.001) and higher LFS (HR 0.83, p = 0.001) compared to MSD. Interval between diagnosis and transplant was the other factor associated with better outcomes (RI (HR 0.62, p < 0.001) and LFS (HR 0.67, p < 0.001)). CONCLUSIONS: Transplantation using UD was associated with better LFS and lower RI compared to MSD for high-risk patients with AML transplanted in first relapse.
Keywords: senioři; Unrelated Donors; Blood Donors; přežívání štěpu; Retrospective Studies; mladiství; Acute myeloid leukemia; Middle Aged; registrace; mužské pohlaví; Graft Survival; nemoc štěpu proti hostiteli; sourozenci; míra přežití; mladý dospělý; Adult; Leukemia, Myeloid, Acute; recidiva; Adolescent; Registries; Hematopoietic Stem Cell Transplantation; Young Adult; Relapse; Disease-Free Survival; ženské pohlaví; transplantace hematopoetických kmenových buněk; retrospektivní studie; Humans; Graft vs Host Disease; Recurrence; Survival Rate; Unrelated donor; lidé středního věku; akutní myeloidní leukemie; Siblings; Matched sibling donor; dospělí; dárci krve; Female; Aged; nepříbuzný dárce; přežití bez známek nemoci; lidé; Male